2016
DOI: 10.15441/ceem.15.028
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of incidental Podostroma cornu-damae poisoning

Abstract: Podostroma cornu-damae is a rare, deadly fungus. However, it can be easily mistaken for antler Ganoderma lucidum. In this case report, two patients made tea with the fungus and drank it over a 2-week period. Both patients presented with bicytopenia, and one patient had desquamation of the palms and soles. Both were treated with prophylactic antibiotics and granulocyte colony-stimulating factor. One patient was admitted to the intensive care unit and received a platelet transfusion. Both patients were discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Although the mechanism by which the toxin acts is unknown, several fatalities associated with this fungus have been reported in Japan. Kim et al [52] described 2 cases in Korea of accidental P. cornu-damae poisoning because the patients mistakenly made tea from the toxic fungus, thinking it was Ganoderma lucidum, a popular health food. Only 1 of the patients experienced alopecia 5 days after initial ingestion, as well as fever, weakness, abdominal discomfort, desquamation of hands and feet, and neutropenia [52].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism by which the toxin acts is unknown, several fatalities associated with this fungus have been reported in Japan. Kim et al [52] described 2 cases in Korea of accidental P. cornu-damae poisoning because the patients mistakenly made tea from the toxic fungus, thinking it was Ganoderma lucidum, a popular health food. Only 1 of the patients experienced alopecia 5 days after initial ingestion, as well as fever, weakness, abdominal discomfort, desquamation of hands and feet, and neutropenia [52].…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al [52] described 2 cases in Korea of accidental P. cornu-damae poisoning because the patients mistakenly made tea from the toxic fungus, thinking it was Ganoderma lucidum, a popular health food. Only 1 of the patients experienced alopecia 5 days after initial ingestion, as well as fever, weakness, abdominal discomfort, desquamation of hands and feet, and neutropenia [52]. Ahn et al [53] reported similar cases, also in Korea, of 2 patients poisoned after mistaking P. cornu-damae for G. lucidum .…”
Section: Resultsmentioning
confidence: 99%
“…1), also called "poison fire coral" or "kaen-take" (in Japanese), is a deadly toxic mushroom native to East Asia, Southeast Asia and Oceania [1][2][3]. Poisoning cases involving T. cornu-damae have been reported [4][5][6][7][8][9][10][11] including fatal cases [4][5][6][7][8]11], and the main toxins in T. cornu-damae have been identified as trichothecene macrolides, specifically satratoxin H and its 12′-acetate, 13′-acetate and 12′,13′-diacetate ( Fig. 2) [12].…”
Section: Introductionmentioning
confidence: 99%
“…The severity of these endotoxic shock-like symptoms depends on the amount of T. cornu-damae ingested. If only a small amount is ingested, these symptoms are mild [7,9,10], but if a lethal amount is ingested, these symptoms are severe and can result in death [4][5][6][7][8]11]. Ingestion of 1 g of T. cornu-damae can be fatal for an adult male [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation